Metastable phase transitions and structural transformations in solid-state materials at high pressure - McMillan, P; Shebanova, O; Daisenberger, D; Cabrera, R; Bailey, E; Hector, A; Lees, V; Machon, D; Sella, A; Wilson, M (2007)
We use a combination of diamond anvil cell techniques and large volume (multi-anvil press, piston cylinder) devices to study the synthesis, structure and properties of new materials under high pressure conditions. The work often involves the study of structural and phase transformations occurring in the metastable regime, as we explore the phase space determined as a function of the pressure, temperature and chemical composition. The experimental studies are combined with first principles calculations and molecular dynamics simulations, as we determine the structures and properties of new phases and the nature of the transformations between them. Problems currently under investigation include structural studies of transition metal and main group nitrides, oxides and oxynitrides at high pressure, exploration of new solid-state compounds that are formed within the C-N-O system, polyamorphic low- to high-density transitions among amorphous semiconductors such as a-Si, and transformations into metastable forms of the element that occur when its "expanded" clathrate polymorph is compressed.